ANALISIS KEAKTIFAN BERORGANISASI TERHADAP PRESTASI AKADEMIK MAHASISWA PROGRAM STUDI TEKNOLOGI LABORATORIUM MEDIS POLITEKNIK KESEHATAN MUHAMMADIYAH MAKASSAR - Syahrani Patunru; Andi Jam'an; Muhlis Madani (UNIVERSITAS MUHAMMADIYAH MAKASSAR, 2020)
This study aims to analyze organizational activeness, the impact, and the advantages and disadvantages of organizational activeness of the students of the Medical Laboratory Technology Study Program of the Muhammaadiyah Health Polytechnic Makassar. This study used qualitative methods with observation data techniques and in-depth interviews with 6 student informants and 1 lecturer. The results showed that the analysis of organizational activeness was to improve: motivation, learning achievement as well as the existence and self-actualization, but the existence and self-actualization were not in accordance with the expectations of students. And organizational activeness can have a positive impact, namely: increased self-confidence, organized time management, honed speaking in public and established good relationships. Where the advantages of being active in organizations can increase the Grade Point Average (GPA) of students, it is proven that almost all scholarship or award recipients are those who are actively involved in the organization.Keywords: Student Organization, Performance Index.